2001
DOI: 10.1159/000052814
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Decline in Vision but Not Hearing Is Associated with Memory Decline in Very Old Adults in a Population-Based Sample

Abstract: Background: Recent cross-sectional research in cognitive aging has demonstrated a robust association between visual acuity, auditory thresholds and cognitive performance in old age. However, the nature of the association is still unclear, particularly with respect to whether sensory and cognitive function are causally related. Objective: This study aimed to determine whether marked declines in performance on screening measures of either visual acuity or auditory thresholds have an effect on cognitive decline o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
118
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(129 citation statements)
references
References 13 publications
9
118
0
2
Order By: Relevance
“…These recent analyses appear to provide at least partial support for previous conclusions based on crosssectional data [35]. Other longitudinal studies report somewhat less consistent significant relations between sensory and cognitive changes [2,5].…”
Section: Correlations Between Sensory Sensorimotor and Cognitive Absupporting
confidence: 62%
“…These recent analyses appear to provide at least partial support for previous conclusions based on crosssectional data [35]. Other longitudinal studies report somewhat less consistent significant relations between sensory and cognitive changes [2,5].…”
Section: Correlations Between Sensory Sensorimotor and Cognitive Absupporting
confidence: 62%
“…Specifically, its goal is to examine six themes in cognitive aging research: (a) the magnitude of mortality-associated and experimental selectivity effects and their relation to age, (b) the degree of convergence between crosssectional and longitudinal age gradients, (c) the ability-specific differences in the magnitude of age-based changes in the longitudinal sample, (d) the acceleration of decline in old-old age, (e) the relation of gender and life-history variables to level and longitudinal change in intellectual functioning, and (f) the differential association of the fluid mechanics and crystallized pragmatics of intelligence with measures of cultural versus biological indicators. In addition to the description of age changes in intellectual functioning in very old age, we also illustrate methodological issues associated with both cross-sectional and longitudinal studies involving old and very old individuals.The present study is closely related to other in-depth longitudinal investigations of intelligence in old and very old age, such as the Australian Longitudinal Study (Anstey, Luszcz, Giles, & Andrews, 2001;Anstey, Luszcz, & Sanchez, 2001), the Seattle Longitudinal Study (Schaie, 1996), the Victoria Longitudinal Study (Hultsch, Hertzog, Dixon, & Small, 1998), and the Kungsholmen project on a population 75 years and over (Hill, Wahlin, Winblad, & Bäckman, 1995; for other longitudinal studies with the focus on old age, see also Colsher & Wallace, 1991;Giambra, Arenberg, Zonderman, Kawas, & Costa, 1995;Schaie & Hofer, 2001;Sliwinski & Buschke, 1999;Zelinski & Burnight, 1997). At the same time, it differs from most of these earlier investigations by a combination of three features: (a) the effect-sized-based quantification of selection effects, (b) the decomposition of these effects into mortality-associated and study components (experimental attrition), and (c) the statistical comparisons of cross-sectional and full-information longitudinal age gradients using latent growth models (LGM).…”
mentioning
confidence: 69%
“…Recent longitudinal data from ALSA [3,4] suggested that independent age-related degenerative processes or pathologies were more likely to account for the association between sensory and cognitive function in normal ageing. Furthermore, findings from a small randomised controlled trial suggested that cataract surgery to correct visual impairment could improve cognitive function between 1 and 16 weeks after surgery in older persons with cognitive impairment prior to surgery [15] .…”
Section: Discussionmentioning
confidence: 99%
“…the Australian Longitudinal Study of Ageing [2][3][4] and the Maastricht Longitudinal Ageing Study [5] . Lindenberger and Baltes [1] postulated three hypotheses to explain this association in the normal ageing population.…”
mentioning
confidence: 99%